2007
DOI: 10.19173/irrodl.v8i1.380
|View full text |Cite
|
Sign up to set email alerts
|

The Current Status of E-learning and Strategies to Enhance Educational Competitiveness in Korean Higher Education

Abstract: The purpose of this study was to examine the current status of e-Learning in Korean higher education and find ways to encourage the further use and development of e-Learning systems that aim to enhance Korea's academic competitiveness. A total of 201 universities in Korea (27 national and public, 163 private, and 11 national universities of education) were examined in this study. At the time of the study, 85 percent of the universities and colleges had investigated implemented e-Learning. There were special e-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 4 publications
2
35
0
4
Order By: Relevance
“…Although e-learning growth has been monumental in terms of quantitative measures, there is an increasing concern for its quality assessment in the context of higher education (Lee, 2006). Added to this, there are specific barriers to the use of e-learning among universities and colleges (Leem & Lim, 2007).…”
mentioning
confidence: 99%
“…Although e-learning growth has been monumental in terms of quantitative measures, there is an increasing concern for its quality assessment in the context of higher education (Lee, 2006). Added to this, there are specific barriers to the use of e-learning among universities and colleges (Leem & Lim, 2007).…”
mentioning
confidence: 99%
“…Unfortunately, this cannot be said of Nigerian universities where students are known to use these devices prevalently for entertainment and gaming and Chen and Denoyelles (2013) strongly supported this finding when they revealed that there is a gap between owning mobile devices and actually using them. The reason for this may be that teachers and students, according to the findings of Leem and Lim (2007), universities are seriously lacking in preparations for mobile learning. The study also found that the benefits of using m-learning devices in learning and teaching business education subjects are many.…”
Section: Discussionmentioning
confidence: 99%
“…In [6], the authors aimed to scrutinize the situation of e-learning in Korea in order to come up with new methods that promote the employment and improvement of e-learning systems. A total of 201 private and public universities in Korea were examined for the purpose of this study.…”
Section: Related Workmentioning
confidence: 99%